Translation and Adaptation Studies: More Interdisciplinary Reflections on Theories of Definition and Categorization - Cattrysse, Patrick (TTR)

(untitled) (Association canadienne de traductologie, 2020)
This paper discusses how theories of definition and probabilistic theories of categorization could help distinguish between translation and (literary film) adaptation, and eventually between translation (TS) and (literary film) adaptation studies (LFAS). Part I suggests readopting the common parlance definition of “translation” as the accurate rendition of the meaning of a verbal expression in another natural language, and “adaptation” as change that leads to better fit. Readopting these common parlance definitions entails categorical implications. The author discusses three parameters: whereas “translation” represents an invariance-oriented, semiotically invested, cross-lingual phenomenon, “adaptation” refers to a variance-oriented phenomenon, which is not semiotically invested, and entails better fit. Part II discusses how theories of categorization could help distinguish between TS and LFAS. The study of the disciplinarization of knowledge involves epistemic and socio-political conditioners. This section concludes that medium specificity, i.e., the linguistic versus lit-film paradigm, plays a major role in separating TS from LFAS. Another player that deserves more attention is the Romantic as opposed to the Classicist value system.